Efecto de la adición del suero de quesería fermentado con Lactobacillus plantarum en la elaboración de pan. - Salazar Robalino, Jhostyn Hernán (2024)
There is currently a growing concern about the shelf life of food products, therefore, some kind of alternative must be found to solve issues such as microbiological deterioration. Bread, due to its composition, has a very limited shelf life, which is why the objective of the research is to analyze the effect of incorporating fermented cheese whey with Lactobacillus plantarum in bread making. For this purpose, three treatments were established whose variable was the concentrations in relation to mass volume, which consisted of 0.25% corresponding to TS1; 0.5% which belongs to TS2; and finally, 0.75% was used corresponding to TS3 where the mass represented the amount of probiotic strain in powder of L. plantarum in 200 ml of pasteurized whey and two control treatments TC and TC2 whose difference lies in that the fermented whey in the preparation of bread was replaced by 200 ml of water in TC while in TC2 200 ml of pasteurized whey without probiotic strain was used. For this purpose, a complete randomized block design and a Tukey test with a significance level of 5% were proposed to determine significant differences between the results of the microbiological analysis and the days of storage of the bread (1, 8 and 15). In addition, a right-sided area hypothesis test was applied for the mean with unknown variance. The advantages of using this strain in the microbiological aspect were defined, mainly the antifungal activity that this strain has. The TS3 treatment resulted in an absence of molds and yeasts on day 15 of the control. In addition, the results suggest that this addition can positively influence aspects such as fat and protein with an increase of 48.94% compared to conventional bread, thus enhancing its nutritional value and minimally reducing humidity from 31.63% of conventional bread to 29.40%, which benefits its conservation. In conclusion, this research has explored the potential of cheese whey fermented with L. plantarum as a beneficial additive in bread making. In addition, to advance further in this field of study, it would be beneficial to explore different fermentation variables and bacterial concentrations to further optimize the quality and safety of the final product.